(untitled) (BIRDEM Medical Journal, 2020)
Autosomal dominant polycystic kidney disease (ADPKD) primarily affects the kidneys; cysts can develop in other organs like liver and pancreas and sometimes complicated with formation of arterial aneurysms, brain being the commonest site. Aortic aneurysms can lead to thromboembolic events. Thromboembolism is also a recognized complication of coronavirus disease 2019 (COVID-19). Here, we present case history of an elderly diabetic, hypertensive patient with bilateral renal stones, who presented with gangrene of the left 5th toe and raised serum creatinine. He was later diagnosed as a case of COVID-19, ADPKD with aortic aneurysm, which was complicated with intraluminal thrombus formation and unfortunately, he died in course of treatment. Birdem Med J 2020; 10, COVID Supplement: 115-119